PERANCANGAN MODEL SISTEM PEMBELIAN TIKET KERETA API BERBASIS KOMPUTER - Harlianto T, Harlianto T; Johan K.W., Johan K.W.; Sofian, Sofian (TESLA Jurnal Teknik Elektro UNTAR, 2006)
This paper discusses the design and implementation of ticketing train system use magnetic card as medium transaction base on computer network. System controlled by computer programming. This device consist of five modules, that is computer, barcode reader, magnetic card reader, printer and electronic door. So it can help the process purchasing ticket in the train stations area for the future.